EDUKASI MENGENAI PENYAKIT GUILLAIN BARRE SYNDROME PADA KADER DI WILAYAH KERJA PUSKESMAS KARANG TALIWANG DAN PUSKESMAS TANJUNG KARANG - Hunaifi, Ilsa; Krisna , I Gusti Lanang; Fitriantoro, Santo; Suryani, Dini; Wardi, Baiq Prita Riantiani; Putri, Siti Noururrifqiyati Juna (Jurnal Abdi Insani, 2024)
Guillain-Barré Syndrome (GBS) is a neurological disorder of the peripheral nervous system and is the most common cause of acute paralysis worldwide. Guillain Barre Syndrome occurs in 1 to 4 patients per 100,000 population worldwide per year and the highest incidence is around 30 - 50 years of age (productive age). Prevention, early detection, and early management of guillain barre syndrome are very important things to do, especially for medical personnel. Community Service for medical personnel of Public Health Care Karang Taliwang and Tanjung Karang began with the implementation of pretest, followed by counselling, and ended with a post test session. This educational activity is aimed at increasing the understanding of cadres in the working area of the karang taliwang health centre about guillain barre syndrome. Keywords: Guillain-Barré Syndrome, education, prevention, early detection